Architectural and solar potential of curved and flat roofs in hot arid regions (with reference to Egypt) - Elseragy, Ahmed A.B. (2004)
This thesis investigates the effect of, various vaulted and domed roof geometries on their solar behaviour under given summer and winter conditions. Roof is the building-envelope element that is most exposed to the sun as it receives a high amount of solar radiation, which is the main cause of summer overheating in hot-arid climates. In addition, to other climatic and physical factors, indoor thermal comfort in hot-arid climates is also influenced by the intensity of solar radiation received by roof surfaces. Therefore, roof form and geometry should be designed with careful consideration to insolation parameters. Domed, vaulted, and curved roofs have been used for a long time in hot-arid regions for historical, cultural, climatic, and structural reasons. The review of previous research work showed that different explanations have been given to the climatic effects of their forms and the environmental behaviour of their enclosed spaces.